Does the rate of orthodontic tooth movement change during the estrus cycle? A systematic review based on animal studies - Noura Saeed Sultan Almidfa; Athanasios E. Athanasiou; Miltiadis A. Makrygiannakis; Eleftherios G. Kaklamanos (BMC, 2021)
Abstract Background As the fluctuation of sex hormone levels in menstruating women results in periodical effects in bone metabolism, understanding the implications for tooth movement could be of benefit to the orthodontist. This type of research presents practical and ethical problems in humans, but animal models could provide useful information. Our objective was to systematically investigate the available evidence on the question whether the rate of orthodontic tooth movement varies between the different stages of the estrus cycle in animals. Methods Unrestricted searches in 7 databases and manual searching of the reference lists in relevant studies were performed up to February 2021 (Medline [PubMed], CENTRAL [Cochrane Library; includes records from Embase, CINAHL, ClinicalTrials.gov, WHO's ICTRP, KoreaMed, Cochrane Review Groups' Specialized Registers, and records identified by handsearching], Cochrane Database of Systematic Reviews [Cochrane Library], Scopus, Web of Knowledge [including Web of Science Core Collection, KCI Korean Journal Database, Russian Science Citation Index, SciELO Citation Index and Zoological Record], Arab World Research Source [EBSCO] and ProQuest Dissertation and Theses [ProQuest]). Our search focused on prospective controlled animal studies, whose samples included female subjects of any species that were quantitatively comparing the amount of tooth movement in the different stages of the estrus cycle. Following study retrieval and selection, relevant data was extracted, and the risk of bias was assessed using the SYRCLE's Risk of Bias Tool. Results From the finally assessed records, 3 studies met the inclusion criteria. Two of the studies experimented on Wistar rats, whereas the other on cats. Tooth movement was induced by expansion or coil springs. The rate of orthodontic tooth movement was increased during the stages of the estrus cycle when oestrogen and/or progesterone levels were lower. The risk of bias in the retrieved studies was assessed to be unclear. Conclusion Hormonal changes during the estrus cycle may affect the rate of orthodontic tooth movement. Although these animal experiment results should be approached cautiously regarding their translational potential, it could be useful to consider the possible impact of these physiological changes in the clinical setting until more information becomes available. Registration: PROSPERO (CRD42021158069).